PENGARUH LITERASI KEUANGAN, MEDIA SOSIAL DAN GAYA HIDUP TERHADAP PENGGUNAAN SHOPEE PAYLATER (STUDI KASUS PADA KARYAWAN PN2 LIQUID PT LAPI LABORATORIES KABUPATEN SERANG) - mila nabila; abdul rauf chaerudin; risma eka desiyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The "buy now, pay later" (BNPL) phenomenon has become a global and local trend, with the growth of BNPL transactions in Indonesia increasing. The purpose of this study is to test the influence of financial literacy, social media, and lifestyle and on the use of Shopee Paylater (Case study on PN2 Liquid employees of PT Lapi Laboratories Serang Regency) both partially and simultaneously. The research method used in this study is a causal associative method with a quantitative approach using SPSS 26 software. The data collection of this study used primary data obtained from the results of questionnaires to 70 respondents. The samples in this study were taken using the Purposive Sampling technique, which comes from the PN2 Liquid part. The test results showed that financial literacy, social media, and lifestyle had a significant effect on the use of Shopee PayLater both partially and simultaneously. These three variables (financial literacy, social media, and lifestyle) have a significant effect on the use of Shopee PayLater with a contribution of 75.9%. These findings emphasize the importance of financial understanding and the role of lifestyle in the adoption of Buy Now Pay Later (BNPL) services, as well as the implications for more comprehensive financial education in the work environment. It can be concluded that Financial Literacy (X1), Social Media (X2), and Lifestyle (X3) have a significant effect on the variables of Shopee Paylater Use (Y) in PN2 Liquid Employees of PT Lapi Laboratries Serang Regency together (simultaneously).